1988
DOI: 10.1111/j.1476-5381.1988.tb11657.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of noradrenaline release from sympathetic nerves in rat anococcygeus muscle by activation of prejunctional β‐adrenoceptors and angiotensin receptors

Abstract: 4 Isoprenaline (0.1 pM) slightly enhanced the S-I efflux of radioactivity, and produced a greater enhancement after neuronal uptake blockade with desipramine (0.03 gM) and a-adrenoceptor blockade with phentolamine (1 pM). 5The facilitatory effect of isoprenaline on S-I efflux of radioactivity was abolished by propranolol (0.3 pM), but was not affected by low concentrations of saralasin (0.03 Mm) or captopril (0.1 Mm) which abolished the effect of angiotensin I. The findings suggest that isoprenaline acts direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…It is out of keeping with the typically absent or rather trifling stimulatory or antiadrenergic neural effects typically seen in humans when angiotensin is infused or the renin-angiotensin system is blocked by angiotensin-converting enzyme (ACE) inhibitors, respectively. There is, in fact, a striking mismatch between these absent or minimal sympathetic neural effects of angiotensin administration and angiotensin blockade in humans (1,16,17,25,43) and the prominent sympathetic neural stimulation produced by angiotensin in laboratory experiments (2,6,10,27,42).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…It is out of keeping with the typically absent or rather trifling stimulatory or antiadrenergic neural effects typically seen in humans when angiotensin is infused or the renin-angiotensin system is blocked by angiotensin-converting enzyme (ACE) inhibitors, respectively. There is, in fact, a striking mismatch between these absent or minimal sympathetic neural effects of angiotensin administration and angiotensin blockade in humans (1,16,17,25,43) and the prominent sympathetic neural stimulation produced by angiotensin in laboratory experiments (2,6,10,27,42).…”
mentioning
confidence: 95%
“…It is out of keeping with the typically absent or rather trifling stimulatory or antiadrenergic neural effects typically seen in humans when angiotensin is infused or the renin-angiotensin system is blocked by angiotensin-converting enzyme (ACE) inhibitors, respectively. There is, in fact, a striking mismatch between these absent or minimal sympathetic neural effects of angiotensin administration and angiotensin blockade in humans (1,16,17,25,43) and the prominent sympathetic neural stimulation produced by angiotensin in laboratory experiments (2,6,10,27,42).One concept of particular clinical interest is the claim that angiotensin receptor blocking agents (ARBs) may, by blocking the presynaptic ANG II type 1 (AT 1 ) receptor, reduce ANG II-mediated facilitation of neurally sustained vascular tone, contributing to the antihypertensive action (3,33). Although in most studies in humans angiotensin administration has not been observed to increase central sympathetic outflow (16), a small but measurable presynaptic stimulatory neural action of angiotensin has been unequivocally demonstrated in the sympathetic nerves of the forearm (5).…”
mentioning
confidence: 96%
“…Since Ang II activates prejunctional receptors located at sympathetic neurons of the rat anococcygeus (Li et al, 1988), we evaluated the nature of these receptors by incubating the tissue in the presence of prazosin, losartan, and PD123319. Prazosin inhibited the Ang II-induced contractions, confirming that Ang II is, in part, an indirect-acting agonist, which could contribute to the apparent noncompetitive antagonism of losartan.…”
Section: De Godoy and De Oliveiramentioning
confidence: 99%
“…Activation of the prejunctional receptor results in enhancement of norepinephrine (NE) release, which induces contractile response by activation of postjunctional ␣ 1 -adrenoceptors (Doggrell and Woodruff, 1978;James and Leighton, 1987;Li et al, 1988). The ultrastructure of nerve terminals in the rat anococcygeus muscle also offers support for a nonadrenergic, noncholinergic enervation of approximately 40% of the nerve terminals (Gibbins and Haller, 1979).…”
mentioning
confidence: 99%
“…Rat and mouse anococcygeus muscles Anococcygeus muscles were set up, as described by Li et al (1988) for rat and by Gibson & Wedmore (1981) for mouse, in 5 ml organ baths for isometric recording and field stimulation (tension: rat, 1 g wt; mouse, 0.3 g wt).…”
Section: Preparation Of Isolated Tissuesmentioning
confidence: 99%